2016
DOI: 10.4323/rjlm.2016.304
|View full text |Cite
|
Sign up to set email alerts
|

Height prediction from ulnar length in Chabahar: a City in South-East of Iran

Abstract: Introduction. Height estimation from the remaining skeleton has a great importance for personal identification in forensic medicine and anthropometric studies. This study emphasized the height estimation from ulnar length in Chabahar population.Objective. One of the most important items in individual identification is estimation of the height from the size of various parts of the body. The aim of this study was to formulate a linear regression equation for the estimation of the stature of the person from the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 15 publications
(20 reference statements)
1
7
0
2
Order By: Relevance
“…Torimitsu et al [29] studied on a Japanese population and reported the larger value of stature, In corpse of the Japanese population by Tormitsu et al [29], it was found that the mean right-ulnar length was 24.16 cm in males and 22.16 cm in females, whereas mean left ulnar length was 24.09 cm in males and 22.04 cm in females. In a study on a city south-east of Iran by Borhani-Haghighi et al [34], it was found that the mean left ulnar length was 29.17 cm in males and 26.47 cm in females. In a study carried out by Okai et al [30] on the Ghanaian students, the mean ulnar length was 29.80 cm in males and 27.3 cm in females.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Torimitsu et al [29] studied on a Japanese population and reported the larger value of stature, In corpse of the Japanese population by Tormitsu et al [29], it was found that the mean right-ulnar length was 24.16 cm in males and 22.16 cm in females, whereas mean left ulnar length was 24.09 cm in males and 22.04 cm in females. In a study on a city south-east of Iran by Borhani-Haghighi et al [34], it was found that the mean left ulnar length was 29.17 cm in males and 26.47 cm in females. In a study carried out by Okai et al [30] on the Ghanaian students, the mean ulnar length was 29.80 cm in males and 27.3 cm in females.…”
Section: Discussionmentioning
confidence: 96%
“…Among these measurements, the stature estimation from long bones becomes imperative, while the direct height measurement is difficult, especially in debilitated, bedridden persons or in persons that may have vertebral column or limbrelated problems [21]. The measurement from long bones includes the upper arm length [22] or humeral length [23,24], tibial length [23,25], femoral length [26], fibula length [25,27], radial length [28][29][30][31] and ulnar length [26][27][28][29][30][31][32][33][34][35] etc. Further, it has also been found that the lower extremities are strongly correlated with stature than upper extremities [36].…”
Section: Introductionmentioning
confidence: 99%
“…Similar were the observations by Bamne et al and Ashish Pande. 5,6,10,11 In the study by Anjali Prasad et al, gender differences in mean height and length of ulna were found to be highly significant and mean ulna lengths of the male were significantly larger than that of the females of all ages. The mean value of length of right and left ulna is statistically insignificant in males and also in females correlating with our study.…”
Section: Discussionmentioning
confidence: 97%
“…In this regard, some other studies were performed to investigate reliable stature formulae according to long bone length. It had been understood that stature equations differ based on various factors such as gender, ethnic group, and study methods (19)(20)(21)(22). Madden et al (2012) claimed that their formula for assessing the height based on the length of ulna correlated closely with the actual height in white participants, while it had failed to provide an accurate assessment of the actual height in black and Asian participants (4).…”
Section: Discussionmentioning
confidence: 99%